2019
DOI: 10.29050/harranziraat.402350
|View full text |Cite
|
Sign up to set email alerts
|

Geleneksel tarhana üretiminde kinoa ununun kullanımı

Abstract: Bu çalışmada tarhananın bazı kalite özelliklerini geliştirmek amacıyla kinoa ununun kullanımı araştırılmıştır. Bu amaçla 6 farklı oranda (% 0, 20, 40, 60, 80 ve 100) kinoa unu, buğday unuyla ikame edilerek, tarhana üretiminde kullanılmıştır. Tarhana örneklerinde bazı fiziksel, kimyasal ve duyusal özellikler araştırılmıştır. Kinoa unu ikamesi ile genel olarak tarhana örneklerinin L*, a* ve b* değerlerinin azaldığı belirlenmiştir. Tarhana formülasyonlarında kinoa unu miktarının artmasıyla, kül, protein, yağ, fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In order to improve the quality characteristics of tarhana in our country, some physical, chemical, and sensory properties were investigated in tarhana produced in different rates (0%, 20%, 40%, 60%, 80%, and 100%) using quinoa flour. According to sensory analysis results, it was determined that the use of quinoa flour had no significant effect on the general acceptability of tarhana formulations (Ucak et al, 2019).…”
Section: Sensory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the quality characteristics of tarhana in our country, some physical, chemical, and sensory properties were investigated in tarhana produced in different rates (0%, 20%, 40%, 60%, 80%, and 100%) using quinoa flour. According to sensory analysis results, it was determined that the use of quinoa flour had no significant effect on the general acceptability of tarhana formulations (Ucak et al, 2019).…”
Section: Sensory Analysismentioning
confidence: 99%
“…Ucak et al (2019) study, the color L* (brightness), a* (redness) and b* (yellowness) values of wheat flour used in making tarhana were found as 93.64, −1.39 and 11.04, respectively while the same values of quinoa flour were 88.01, −0.27 and 13.24, respectively and the L, a* and b* values of tarhana samples made with quinoa flour substitution were determined to decrease. The color values we obtained in our study were found to be compatible with the values obtained in the literature.…”
mentioning
confidence: 99%